Microbial contmination and Safety of Some Leafy Green Vegetables - Jabbar Farhan Al-maadhidi; Osama Bassim Al-Saffar; Sabah Saad Abdulsahab; Ali Dawood (Journal of Madenat Alelem University College, 2015)
Leafy green vegetable consumed fresh daily, it was evaluated for inhabitant of pathogens and investigated for safety clearance. Vegetable were washed with tap water, Potassium Permanganate, and liquid detergent separately for 1,3, and 5 minutes inorder to find the right treatment and get germ free vegetables. Results showed all investigated vegetables (Celery, Parsly and Pepper cress) were contaminated with pathogenic microbes according to contamination indicator.Washing with tap water alone and with 1% liquid detergent for three minutes and more let to remove all pathogenic bacteria only rather than parasite. Parasite linkage is so strong which resist washing with tap water or with detergent. Optimum condition to get rid of all hygienic pathogens (Bacteria, Parasites) isneed to wash with Potassium permanganate solution of 0.5% for three minutes or with 1% for one minute.